(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Sleep – this natural urge is so essential phenomenon of life that engages our one third of life-span, still indulging in being slept is mystery to everyone. At one side adequate sleep quality imparts fair concentration, emotional, cognitive motivational harmony inside body’s mind, soul and consciousness. Contrary to which inadequate sleep or poor sleep quality leads to tiredness, lack of focus, exhaustion, a low pain tolerance, anxiety, irritational thoughts, hallucinations, loss of appetite, constipation and many more. Sleep has a positive impact over digestion, metabolism, nourishment and health. It is irresistible, irreplaceable and unique boon for us, which is pillar of our life. The natural cycle of sleep and awakening is depending on Awastha of Sharir Dosha, Kaal Dosha, and few more factors as depicted in Ayurveda texts. So, the quality of sleep depends on these factors. If there is Kshaya of Kapha, or Vriddhi of Vata and Pitta, then the quality of sleep disturbs. In the realm of holistic well-being, Ayurveda, the ancient Indian system of medicine, offers profound insights into optimizing sleep quality. Through personalized approaches, Ayurvedic remedies like herbal formulations, lifestyle modifications, and relaxation techniques aim to rebalance Doshas and promote restful sleep. Integrating practices such as meditation, gentle yoga, and consistent sleep routines can pacify Vata and Pitta Dosha, calm the mind, and induce relaxation, fostering deeper and more rejuvenating sleep. Ayurveda’s holistic perspective provides a natural and sustainable pathway to address poor sleep quality and promote overall well-being. The present paper is here to discuss in detail about Sukh Nidra.